2015
DOI: 10.1097/rlu.0000000000000370
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Near-the-Injection-Site Sentinel Nodes in Head and Neck Melanomas With a High-Resolution Portable Gamma Camera

Abstract: A high-resolution PGC, positioned close to the skin, is able to detect SNs at distances of at least 3 mm from the injection site. A further clinical evaluation of this device to establish its added value in reducing false-negative procedures and potential recurrences is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Also, SLNs may be hidden by the injection site, as is often observed in malignancies in the head and neck region (shine-through phenomenon). In these challenging settings, using three-dimensional imaging and navigation [97][98][99] or a portable gamma camera [100][101][102] may improve intraoperative detection of SLNs.…”
Section: Gamma Camerasmentioning
confidence: 99%
“…Also, SLNs may be hidden by the injection site, as is often observed in malignancies in the head and neck region (shine-through phenomenon). In these challenging settings, using three-dimensional imaging and navigation [97][98][99] or a portable gamma camera [100][101][102] may improve intraoperative detection of SLNs.…”
Section: Gamma Camerasmentioning
confidence: 99%
“…Aside from fhSPECT navigation, there are other possibilities for intraoperative sentinel node imaging such as portable gamma cameras [21][22][23][24] and fusion ultrasound/…”
Section: Emerging Developments For Sln Biopsy In Hn Cancermentioning
confidence: 99%
“…Moreover, they provide a visual real-time feedback when localizing SLNs and confirming their successful resection. For the most frequently used portable gamma camera (Sentinella, Oncovision, Valencia, Spain), promising results have been published for SLNB in HN malignancies [36][37][38][39] and urogenital cancers [40][41][42][43][44][45]. Portable gamma cameras can reliably detect deep-lying nodes and SLNs with only low tracer accumulation.…”
Section: Toward Intraoperative 3d Imagingmentioning
confidence: 95%
“…Unlike a gamma probe, intraoperative imaging can identify SLNs lying next to the injection site or distinguish multiple SLNs located next to each other [39,46]. Recently, a simulation model demonstrated that SLNs can be detected at a distance of 3 mm from the injection site owing to the high resolution of the pinhole collimated system [39]. Mobile large FOV gamma cameras may be used if a complex anatomic region is to be covered within one image acquisition [34].…”
Section: Toward Intraoperative 3d Imagingmentioning
confidence: 98%
See 1 more Smart Citation